La edición del Regalo de la Vida Humana [Österreichische Nationalbibliothek, Codex Vindobonensis Palatinus, Ms. 11160] de Juan Vallés (c. 1496-1563): Un proyecto en curso - Serrano Larráyoz, Fernando (Huarte de San Juan. Geografía e Historia, 2006)
We present here an advance of a project actually in process, the edition of Regalo de la Vida Humana, (Austrian National Library) one of the less know works of Juan Vallés (c. 1496-1563), former Treasurer of the kingdom of Navarra. New features about his family origins are provided, and also about his professional activities, related with the Chancellor Office in Aragón and latter with the Treasurer Office in Navarra. The main characteristics of this book, which will be edited shortly by the Government of Navarra, are also pointed out.